Peran Account Officer Dalam Analisis Kelayakan Pengajuan Pembiayaan Murabahah - Meisa Tara; Atika Riasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Murabahah financing is one of the most popular types of financing for customers who do not escape the role of the account officer in the analysis of determining the feasibility of applying for murabahah financing. There are differences in the total number of customers who apply for murabahah financing and the total realization of murabahah financing, in that customers who apply for murabahah financing are not always accepted by the account officer. Financing was rejected because there were customers who did not meet the eligibility assessment on character, capacity and collateral. If the feasibility assessment in several aspects is not fulfilled, the customer is deemed unfit to be provided with financing.This research aims to determine the role of account officers in determining the feasibility of applying for murabahah financing at BPRS Metro Madani KC Unit II Tulang Bawang. This type of research is field research, while the nature of the research is descriptive qualitative. Data collection techniques through interviews and documentation. After the data was obtained, the data was analyzed using inductive thinking methods.The research results show that account officers play a role in managing accounts, managing products, managing financing, managing sales and managing profitability. And the account officer has carried out his role well in determining the feasibility of applying for murabahah financing in accordance with theory, namely using 5C analysis, although in terms of character, capacity and economic conditions in practice it has not been carried out optimally.